Farmers in the Forest Economic Development and Marginal Agriculture in Northern Thailand - Kunstadter, Peter R.; Chapman, Edward Char; Sabhasri, Sanga (University of Hawai'i Press, 1978)
Farmers in the Forest, while using examples chiefly from northern Thailand, is concerned with complex problems found in all tropical countries. In these areas rapid population growth, increasing demands for food, and burgeoning international markets for forest products and other raw materials are associated with active competition for land and natural resources in upland areas. This book brings together studies by administrators, agronomists, anthropologists, forest ecologists, geographers and jurists, who describe a variety of swidden systems and their effect on soil, forest, society, and economy. They point to conflicts between traditional farming systems and modern legal and administrative constraints now being imposed, and they describe special and technological conditions that contribute to a marginal, stagnant upland economy, increasing socio-economic disparities with the lowlands, and the serious ecological consequences of these conditions. Several possible solutions are suggested to solve these problems.